130 Development of a pesticide crop/livestock exposure matrix using data from three agricultural cohort studies in the AGRICOH consortium. (11th October 2013) - Schinasi, L S; Freeman, Beane; Baldi; Kromhout; Lebailly; Nordby; Kjaerheim; Brouwer; Alavanja; Schuz; Leon
Abstract : Objectives: Excess risk of lympho-hematopoietic malignancies has been documented in farmers. Although numerous studies have investigated associations of various pesticides with lympho-hematopoietic malignancies, results have been inconsistent. A crop/livestock-exposure matrix for estimating exposures to pesticides is being developed for a pooled analysis of lympho-hematopoietic malignancies in farmers. Methods: Data arise from the United States Agricultural Health Study (AHS), the French Agriculture and Cancer Study (AGRICAN), and the Cancer in the Norwegian Agricultural Population Study. When study data are unavailable, historical information on region and crop/livestock specific pesticide use are being gathered from agricultural records, experts, and the French PESTIMAT matrix. Selection of matrix axes is based on information availability and importance in predicting pesticide exposures; of crop/ livestock categories is based on major commodities in each country and common production across or frequent production within the cohorts; and of chemical groups is based on frequency of use and a priori expectations of associations with lympho-hematopoietic malignancies. Results: The cohorts contain varying levels of exposure information. AHS contains information on ever lifetime chemical use for 52, 394 private applicators. AGRICAN contains data on crops/livestock ever produced in the lifetime of 182, 132 farmers. For each 10-year agricultural census from 1969–1989, the Norwegian cohort contains data on crops/livestock farmed by 248, 000 farmers and spouses. Matrix axes will be defined by time period, crop/ livestock produced and pesticide chemical group. Matrix cells will be filled with pesticide use information by chemical group and, if possible, chemical substance. Crop/ livestock groups will include major categories such as corn, grains, potatoes, soybeans, tobacco, vineyards, poultry, beef cattle, dairy cattle, swine and sheep/goats. Conclusions: This work demonstrates the development of a pesticide exposure matrix using pooled data from multiple countries, which will be used for the largest evaluation of pesticides and lympho-hematopoietic malignancies to date.